Does Entrepreneurship Education, Motivation, Ability, Attitude and Social Factors Influence Entrepreneurship Intentions in Indonesia? - Arman, Hj. Ahmad; Rizal Ula, Ananta Fauzi; Maria, Romeli; Ilham, Sentosa; Che Rosmawati, Che Mat; Mohd. Farid, Shamsudin (2021)
The high unemployment in high school and university graduate students is a problem that must be solved by the Indonesian government. Various methods are used to reduce the unemployment rate for college students, one of them is by fostering students' intention in entrepreneurship. College students Entrepreneur intentions are expected to be able to grow entrepreneurs who can open jobs. To push entrepreneurship intention, many factors affect students' entrepreneurship intentions. This research is conducted to find out the determinants of student entrepreneurship intentions. This research uses quantitative research with multiple regression statistical analysis with a sample of 221 respondents. The results of the study found that entrepreneurship education influences entrepreneurship attitudes but does not affect entrepreneurship intentions, motivation influences entrepreneurship attitudes and entrepreneurship intentions, ability influences entrepreneurship attitudes but does not affect entrepreneurship intentions, social factors, and entrepreneurship attitudes affect entrepreneurship intentions. The dominant factor affecting entrepreneurship intentions is the entrepreneurship attitude that the campus and the government have inculcated the spirit of a good entrepreneurship attitude by creating entrepreneurship education and training methods as well as conducting mentoring for final semester students as prospective entrepreneurs and beginners entrepreneurs.